Transformasi Pendidikan di Komunitas Petani: Menyusun Kurikulum untuk Pemberdayaan Petani - Abdul Aziz, Nurdin (CV RIFAINSTITUT, 2024)
This study aims to examine the transformation of education within farming communities and how an education curriculum can be developed to support the empowerment of farmers in the modern era. In the context of agriculture, which is constantly evolving, the importance of relevant and sustainable education is essential for improving farmers' welfare. Using a qualitative approach, this research analyzes the challenges, needs, and potential within farming communities in facing social and economic changes. The main focus of this study is to identify key elements in the curriculum that can empower farmers to adopt environmentally-friendly agricultural technologies, enhance entrepreneurial skills, and strengthen their social capacities to build self-reliant communities. The findings of this research are expected to contribute to the development of agricultural education policies that are more aligned with the real needs on the ground and strengthen food security at the community level.